2009
DOI: 10.1086/605676
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Compensated Hepatitis C Virus–Related Cirrhosis in HIV‐Infected Patients

Abstract: The incidence of clinical liver events in HIV-HCV-coinfected patients with CPT class A compensated cirrhosis is close to that previously reported in HCV-monoinfected patients. Lower baseline CD4 cell counts, lack of therapy against HCV, and higher CPT score are the factors related to the occurrence of clinical liver events. Minimal changes in CPT score have strong impact in the prognosis of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 32 publications
1
48
2
Order By: Relevance
“…37 The impact of anti-HCV therapy on the survival or the risk of decompensations in HIV/HCV-coinfected patients with compensated cirrhosis has been only assessed in two previous cohort studies with apparent conflicting data. 33,38 In the present study, neither exposure to HCV therapy nor achieving SVR during follow-up were associated with a lower risk of developing decompensations. On the contrary, achieving SVR during follow-up tended to be associated with an improved survival in univariate analyses and exposure to therapy during follow-up was associated with a lower risk of death of any cause.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…37 The impact of anti-HCV therapy on the survival or the risk of decompensations in HIV/HCV-coinfected patients with compensated cirrhosis has been only assessed in two previous cohort studies with apparent conflicting data. 33,38 In the present study, neither exposure to HCV therapy nor achieving SVR during follow-up were associated with a lower risk of developing decompensations. On the contrary, achieving SVR during follow-up tended to be associated with an improved survival in univariate analyses and exposure to therapy during follow-up was associated with a lower risk of death of any cause.…”
Section: Discussioncontrasting
confidence: 57%
“…Interestingly, MELD score was associated with overall mortality but not with liver-related mortality after multivariate analyses in our study. In fact, the predictive value of MELD score in HIV/HCV-coinfected patients remains controversial, with previous studies reporting no independent association with survival 6,33 and others finding such an association. 34,35 In our opinion, the lack of an independent association of MELD with liver-related mortality in our cohort could reflect a weaker predictive value in the long term, as is the case in this study, than in the short-and mid-term.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of liver disease in HIV-positive patients is caused by coinfection with the hepatitis C virus (HCV) [1][2][3]. Coinfection with HIV and HCV is associated with accelerated liver fibrosis and shorter time to progression to cirrhosis and hepatic decompensation when compared with those with HCV monoinfection [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…15 Numerous studies have shown an accelerated fibrosis progression rate as well as more frequent decompensation and death once cirrhosis is present. 5,14,[16][17][18] These characteristics highlight the importance of early recognition and treatment of HCV in HIV coinfection. Accordingly, the American Association for the Study of Liver Diseases (AASLD)/Infectious Diseases Society of America (IDSA) HCV guidance document identifies patients with HIV coinfection as a priority population that should be treated for HCV without regard to fibrosis stage.…”
Section: Epidemiology and Natural History Of Hepatitis C Virus In Patmentioning
confidence: 99%